Penerapan Promotion mix pada Pujasera Pasir Putih - Immanuel Zai; Ricky Ricky (Jurnal Pengabdian Masyarakat Akademisi, 2023)
The community service activity aims to apply Promotion Mix to the White Sand Food Court. Data collection technic in this activity using qualitative methods case study. The community service activity output in the form of social media accounts, websites, menus, and brochures for promotion. The implementation of promotion mix shows that there has been an increase in terms of company turnover in beverage sales in the last three months, namely October, November, and December.